Roman bishops and the development of church-administrative structures at the “superprovincial” level at the beginning of the 5th century - Mikhail Gratsianskiy (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article analyses three epistles of Popes Innocent I (402–417) and Zosimus (417–418), which endow the primates of Antioch, Thessalonica and Arles with special prerogatives. These epistles are of interest from the point of view of the church-administrative model, which for various reasons was promoted by these popes in the aforementioned churches. The use of this model is seen as a concrete practical expression of a certain stage in the development of the concept of papal primacy of power, which was based on the idea of the exclusive “apostolic” status of the Roman see. In fact, it was about the creation of special ecclesiastical and administrative districts, vertically integrated with the Roman see, in which the popes assumed a modification of the system of administration, providing for the emergence of the figure of the bishop-primate at the “superprovincial” level, and for the special jurisdiction of this bishop. In relation to each of the regions, this model had some peculiarities, expressed in the way of functioning of the synodal institutions, the role and place of the metropolitans, and the relationship of the primate with the Roman see.